2015
DOI: 10.1155/2015/256580
|View full text |Cite
|
Sign up to set email alerts
|

CandidaBloodstream Infections in Italy: Changing Epidemiology during 16 Years of Surveillance

Abstract: Although considerable progress has been made in the management of patients with invasive fungal infections, Candida bloodstream infections are still widespread in hospital settings. Incidence rates vary geographically, often because of different patient populations. The aim of the present study was to describe the epidemiology of candidemia, to analyze the trend of species distribution, and to measure the in vitro susceptibility to antifungal drugs in a university Italian hospital from 1998 to 2013. The antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 30 publications
8
54
1
8
Order By: Relevance
“…Our results indicate a relatively high rate when compared with recent studies that reported a rate of 3.06 per 10,000 admissions in an Italian general ward (18) and 15.1 per 10,000 admissions in a Chinese ICU population. (24) This variability in the incidence rates of candidaemia among different countries may be reflective of differences in their healthcare systems, patient backgrounds and/or surveillance methods.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Our results indicate a relatively high rate when compared with recent studies that reported a rate of 3.06 per 10,000 admissions in an Italian general ward (18) and 15.1 per 10,000 admissions in a Chinese ICU population. (24) This variability in the incidence rates of candidaemia among different countries may be reflective of differences in their healthcare systems, patient backgrounds and/or surveillance methods.…”
Section: Discussioncontrasting
confidence: 47%
“…‡Although the criteria for the severity of disease were not clear, it was defined as an Acute Physiology and Chronic Health Evaluation (APACHE) II score > 20 in the present study, as an APACHE II score > 20 during candidaemia was found to be associated with an elevated mortality rate in a previous study. (18) cumulative number of risk factors for invasive candidiasis had the larger AUROC.…”
Section: Resultsmentioning
confidence: 93%
“…Recent studies detail that invasive candidiasis is the leading cause of mycosis-associated mortality worldwide [4][5][6][7]. Although the opportunistic pathogen Candida albicans is the most common species found in the hospital environment, numerous non-albicans Candida (NAC) species have been isolated from patients as a source of primary infection [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…5 In a 16-year surveillance study, 394 cases of candidemia per 10,000 admissions have been reported from an Italian hospital where Candida albicans was present in 44.2% cases, followed by Candida parapsilosis and Candida glabrata. 6 A surveillance study from a Mexican tertiary care center on BSI revealed that C. albicans (46%) and Candida tropicalis (26%) were dominant among other species, whereas C. glabrata was more prevalent in diabetic and old age persons. 7 Non-albicans Candida (NAC) species were predominant in HIV seropositive patients admitted at HAART center in Gujarat, followed by C. albicans.…”
Section: Introductionmentioning
confidence: 99%